Molecular detection of some virulence genes of Klebsiella pneumonia isolated from Camels - Alkaabawi, Naer A; Ayyez, Hayder N.; Mutar, Halah M. (Archives of Veterinary Science, 2025)
Klebsiella pneumonia is internationally recognized as one of the most important microorganisms that causes defect in economic importance to the dairy industry, affecting almost all domesticated species of animals and being reported from all over the world. This study aimed to detect K. pneumonia isolated from Camels and studying some serious virulence factors of k. pneumonia in comparison with those isolated from different animals. Sixty nasal and fecal samples were collected from camels. Many isolates on MacConkey were in different colors on chrome orientation media, the results on this differential media showed primary identification of 55 % Klebsiella, 21 % E. coli, 15 % Enterococcus, and 9 % Pseudomonas. However, the quantitative PCR for (16S rRNA) confirmed (82%) of total suspected isolates were K. pneumonia. Multi-sequences alignment of this sequenced isolate showed a high identical score to K. pneumonia strains from Hong Kong and Nigeria. The results also showed 100% of K. pneumonia isolates were resistant to Vancomycin and highly sensitive toward the others like Levofloxacin, Trimethoprim, and Ceftriaxone. The molecular detection results for some virulence factors genes (ESBL) showed variable differences of these genes in comparison with recently reported research on bovine such as (90% CTX, 100% INT1, 60% INT2, 60% KPC, 10% HEMO and 0% of SHV). It was concluded that the livestock and body immune of camels that less exposure to antibiotics plays an important role in restraining the development of the resistance systems of K. pneumonia towards antibiotics.